Xenograft models for adrenocortical carcinoma. (5th February 2016) - Hantel, Constanze; Beuschlein, Felix
Abstract: Adrenocortical carcinomas (ACCs) are rare, heterogeneous and very malignant endocrine tumors with a poor prognosis. An important prerequisite to optimize existing therapeutic regimens and to develop novel therapeutic strategies are preclinical disease models. In recent years molecular and genetic profiling of surgical tumor specimen led to the identification of novel interesting markers. However, precise involvement of these markers in tumorigenesis and their functional relevance in therapeutic outcome is still under investigation. Xenograft models are important tools for such functional studies as they bear the potential to mimic the complexity of solid tumors including tumor cells, stroma and blood vessels. Thus, for the successful and safe development of novel therapeutic strategies xenograft models remain to be indispensable experimental tools. Here we provide an overview on currently existing xenograft models for ACC, their tissue origins, establishment, implications as well as limitations. Highlights: We provide an overview on currently existing xenograft models for ACC. We include classical xenograft models as well as alternatives and recently achieved progress. We discuss the specific tissue origins, establishment, implications as well as limitations.